Targeting F-Box Protein Fbxo3 Attenuates Lung Injury Induced by Ischemia-Reperfusion in Rats - Hung, Kuei-Yi; Liao, Wen-I; Pao, Hsin-Ping; Wu, Shu-Yu; Huang, Kun-Lun; Chu, Shi-Jye (Frontiers in Pharmacology, 2019)
Background: Increasing evidence suggests that Fbxo3 signaling has an important impact on the pathophysiology of the inflammatory process. Fbxo3 protein inhibition has reduced cytokine-driven inflammation and improved disease severity in animal model of Pseudomonas-induced lung injury. However, it remains unclear whether inhibition of Fbxo3 protein provides protection in acute lung injury induced by ischemia-reperfusion (I/R). In this study, we investigated the protective effects of BC-1215 administration, a Fbxo3 inhibitor, on acute lung injury induced by I/R in rats. Methods: Lung I/R injury was induced by ischemia (40 mins) followed by reperfusion (60 mins). The rats were randomly assigned into one of six experimental groups (n=6 rats/group): the control group, control + BC-1215 (Fbxo3 inhibitor, 0.5 mg/kg) group, I/R group, or I/R + BC-1215 (0.1, 0.25, 0.5 mg/kg) groups. The effects of BC-1215 on human alveolar epithelial cells subjected to hypoxia-reoxygenation (H/R) were also examined. Results: BC-1215 significantly attenuated I/R-induced lung edema, indicated by a reduced vascular filtration coefficient, wet/dry weight ratio, lung injury scores, and protein levels in bronchoalveolar lavage fluid (BALF). Oxidative stress, and the level of inflammatory cytokines in BALF were also significantly reduced following administration of BC-1215. Additionally, BC-1215 mitigated I/R-stimulated apoptosis, NF-B, and mitogen-activated protein kinase activation in the injured lung tissue. BC-1215 increased Fbxl2 protein expression, and suppressed Fbxo3 and TNFR associated factor (TRAF)1-6 protein expression. BC-1215 also inhibited IL-8 production and NF-B activation in vitro in experiments with alveolar epithelial cells exposed to H/R. Conclusions: Our findings demonstrated that Fbxo3 inhibition may represent a novel therapeutic approach for I/R-induced lung injury, with beneficial effects due to destabilizing TRAF proteins